Recent Advances in Gearing Scientific Theory and Applications - Radzevich, Stephen P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents the most up-to-date accomplishments in gear design and gear production, detailing theory of gearing and its application. As an enormous number of gears are used in such sectors as automobiles, aerospace, machines, and similar industries, even a very small improvement in the gear design or production, for example a 10 cent savings on each gear, can result in huge of savings in manufacturing, underscoring critical importance of the subject of the book. Giving a solid background in theory together with the latest advances in design and production, the book is ideal for product designers working in numerous industries. The volume also serves as a useful supplement to required texts well for students in mechanical and industrial engineering as it helps establish a scientific foundation to the subject, and facilitates a systematic learning process of gear kinematics, gear geometry, gear design, gear production/finishing operations, and related competencies.
Kinematical Foundations of Scientific Classification of Gearing -- Conjugate Surfaces: State-of-the-Art (A Scientific Overview) -- Hyperboloidal Hobs: Design and Production -- Kinematic Pairs: Novel Kinds and a Scientific Classification -- Achievements in Investigation and Application of Plastic Gears -- Application of Task Based Conceptual Design Method for Surface Reproduction Mechanisms -- Fundamental Accomplishments in Scientific Theory of Gearing -- Theory and applications based on S-gear geometry.
Keywords: Machinery; Automotive engineering; Aerospace engineering; Astronautics; Engines; Machinery and Machine Elements; Automotive Engineering; Aerospace Technology and Astronautics; Engine Technology; Gearing